Testing the use of continental standardized growth curves (SGCs) for De estimation on coarse quartz grains from Lake Woods, Northern Australia - Rui, Xue; Li, Bo; Cohen, Tim J. (Frontiers in Earth Science, 2022)
Using continental SGCs built by Fu et al. (2020) can save significant machine time for constructing SGCs when compared to traditional SGC methods which need significantly more time for building sample-specific or regional SGCs. In this study, the reliability of continental SGCs is tested using coarse quartz grains (180–212 µm) from Lake Woods in Northern Australia. De values obtained by continental SGCs are consistent with De values obtained by the regional SGCs and by the SAR procedures.